ISSUES OF IMPROVING THE ECONOMY OF HEALTHCARE IN THE RUSSIAN REGIONS - M. V. Panasyuk; R. D. Dasayeva (Russian Journal of Economics and Law)
Objective: to identify problems in the field of healthcare economy of Russian regions nowadays and to determine the ways of their solution. Methods: descriptive, comparative, graphic and statistical methods. Results: classification of indicators of the health care system development in the region is proposed; comparative analysis of the health care system indicators of the Tatarstan Republic and Russian regions is carried out; the approach to the organization of the health care system in Cuba is described; a number of measures to address the major economic problems of the health care system of the region are proposed. Scientific novelty: comparative characteristics is presented and analysis of development of regional healthcare system is made, the ways to solve these problems are proposed. Practical value: the ways of optimization of the healthcare system of the region are described.